2010
DOI: 10.1063/1.3501108
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically induced structural reorientation in magnetite studied by nuclear magnetic resonance

Abstract: Phenomenon related to low symmetry phase of magnetite Fe3O4 below the Verwey transition is the switching of magnetic easy axis by external magnetic field connected with a structural transition. Results of nuclear magnetic resonance (NMR) studies of axis switching are presented, preceded by careful characterization by magnetic measurements. We detect changes in the F57e NMR spectra that evidence the structural transition interrelated with the axis switching. We also observe the switching process in time and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…Similar low-temperature (low-T ) processes were revealed by microscopic probes [40,41] for samples prepared in a different way. Thus, electronic processes that cause diffuse scattering result from the intrinsic properties of magnetite, and not from particular preparation conditions.…”
Section: Methodssupporting
confidence: 55%
“…Similar low-temperature (low-T ) processes were revealed by microscopic probes [40,41] for samples prepared in a different way. Thus, electronic processes that cause diffuse scattering result from the intrinsic properties of magnetite, and not from particular preparation conditions.…”
Section: Methodssupporting
confidence: 55%
“…These might be either electron tunneling and electron hopping processes [64], glassy polar degrees of freedom [46] or thermally activated structural processes [39]. A comparison of the activation energies of the dielectric Debye process (31 meV (this work), 40 meV [49]), of easy-axis switching (25-33 meV [10,39]) and of domain-wall motion in single crystals (40 meV [65]) indicates a connection between these phenomena. Since the easy-axis direction is stabilized by the film-substrate strain, it would be easier to observe a ferroelectric polarization in thin films than in bulk.…”
Section: Discussionmentioning
confidence: 66%
“…• Studies of the easy-axis switching in magnetite [10,[38][39][40] revealed thermally activated behavior with an activation energy in the range 25-33 meV.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is surprising that the electric polarization does not already develop at the VT. This is because in between 40 K and T V , the electric polarization is suppressed by relaxation processes due to electron tunnelling and electron hopping processes [53], glassy polar degrees of freedom [54], or thermally activated structural processes [55]. Since the easy-axis direction is generally stabilized by the film-substrate strain, it would be easier to observe a ferroelectric polarization in thin films than in bulk.…”
Section: Multiferroic Propertiesmentioning
confidence: 99%